Effect of diets on growth and survival rate of russian sturgeon (Acipenser gueldenstaedtii Brandt, 1833) from fry to fingerling - Le Trang, Tran Thi; Thuy, Nguyen Viet (Academia Journal of Biology, 2014)
Diet is one of the important factors having strong effects on growth rate, survival rate and rearing efficiency of many fish species in general and Russian sturgeon in particular. In this study, three different diets (CT1-Artemia and processed; CT2-Lansy and Skerting; CT3-Artemia, Lansy and Tubifex worm) were experimented in order to identify the most suitable diets for rearing Russian sturgeon from the stages of fry to fingerling. The fish were reared in the raceway system in a period of four weeks. Results showed that the diets had strong effects on growth and survival rates of Russian sturgeon. In which, the fish were fed on the formula CT3 gave the highest absolute growth rate and final body weight (0.2 g/ind./day; 4.04 g/ind.), followed by the formula CT1 (0.17 g/ind./day; 3.52 g/ind.) and lowest at the formula CT2 (0.13 g/ind./day; 3.02 g/ind.) (P<0.05). Similarly, the fish were fed with the formula CT3 obtained higher relative growth and survival rates compared to those of the formula CT2 (54.59%; 69.33% as opposed to 42.6%; 37.67%; P<0.05). However, there were no significant differences about these two parameters between the formula CT3 and those of the formula CT1 (48.58%; 69%) (P>0.05). From the results of this study, it can be suggested that the formula CT3 was the most appropriate diet for rearing the Russian sturgeon from the stages of fry to fingerling under Lam Dong conditions.